Erring from Good Huswifry? The Author as Witness in Margaret Cavendish and Mary Trye - Clairhout, Isabelle (Renaissance and Reformation / Renaissance et Réforme, 2014)
Margaret Cavendish and Mary Trye differ in the extent to which their scientific ideas and social positions allowed them to translate their view of the embodied observer into a steady textual image that was consistent with their methodological and epistemological ideas. However, they are united in a rhetoric of opposition that accommodates their defence against accusations that females had no authority in these matters due to inferior physical and mental qualities (although Cavendish’s defence is far from unequivocal). Moreover, both took on the role of a spokesperson for a member of their family and, again, their interpretation of that role is affected by their scientific views. This article will examine the similarities and differences of their authorial self-fashioning in the context of what was far from homogeneous early modern scientific authorship.